Testate amoebae (Protists) as palaeoenvironmental indicators in peatlands - Lamentowicz, Mariusz; Mitchell, Edward (My University, 2005)
Testate amoebae (or testaceans, Testacea, Arcellaceans) are unicellular eukaryotic organisms living in freshwater or most terrestrial habitats such as soils, mosses, lakes, rivers, as well as brackish habitats such as estuaries. They are very abundant in Sphagnum mosses, where they live in the top part of mosses and the oxygenated part of the peat. The tests (shells) of Tesiacea are well preserved in peat and to a lesser extent in lake sediments. Efforts should be concentrated on constructing reliable regional transfer functions (mathematical representation of relation of species to environmental variables — presence of particular taxa in fossil material is the function of past environmental pa- rameters). as they exist for some world areas, and there is a complete lack of them for central Europe. Polish data are ex- ceptionally important because Poland is under several contrasted climatic influences — from oceanic to continental. The comparison of our data on climatic tendencies with those from Western Europe and the rest of the world will show how similar or different the responses of Polish peatlands might be. The paper has three aims: (a) to present the need for ecological studies on testate amoebae in Central Europe, (b) to show the potential of reconstruction of past environment on the basis ofmultiproxy studies that include testate amoebae as an in- tegral part of the palaeoecology toolbox and (c) to put our research efforts on testate amoebae in Poland in a more global perspective.
Keywords: Sphagnum-domm&ted peatlands; testate amoebae; protozoa; transfer function; pollen analysis; Holocene; palaeo-ecology; hydrology; climate; Tuchola Pinewoods